Urgensi Konselor Sebaya dalam Menginternalisasikan Nilai-nilai Moderasi Beragama - Monika, Ika; Juwita, Melly (Indonesian Journal of Educational Counseling, 2024)
The diversity of ethnicity, religion, and race in Indonesia presents potential challenges in today's society. There is a possibility that the millennial and Gen Z generations may not fully grasp the importance of moderation in religious values. The urgency of peer counselors in internalizing religious moderation could be one approach to instilling values such as tolerance, thus averting triggers for conflict. The purpose of this writing is to highlight the importance of peer counselors in internalizing religious moderation values. This study adopts a literature review method, specifically a library research approach, where relevant literature indexed by Google Scholar within the last five years (2019-2024) is examined. The findings reveal that peer counselors play a crucial role in internalizing religious moderation values. By doing so, they contribute to conflict prevention, promote tolerance, and mitigate discrimination based on differing opinions or religious beliefs. Peer counselors internalizing religious moderation values represent a preventive measure against issues within religious moderation..